War, guilt, and world politics after World War II - Berger, Thomas U. (Cambridge University Press, 2012)
More than sixty years after the end of World War II it continues to wrestle with the legacies of the Third Reich, offering long-overdue compensation to the hundreds of thousands of former slave laborers while arguing with the governments of Poland and the Czech Republic over how to commemorate the millions of ethnic Germans who were driven out of Eastern Europe in the aftermath of the war.